Intravenous Sphingosylphosphorylcholine Protects Ischemic and Postischemic Myocardial Tissue in a Mouse Model of Myocardial Ischemia/Reperfusion Injury - Christine Herzog; Martina Schmitz; Bodo Levkau; Ilka Herrgott; Jan Mersmann; Jan Larmann; Kai Johanning; Michael Winterhalter; Jerold Chun; Frank Ulrich Müller; Frank Echtermeyer; Reinhard Hildebrand; et al. (Hindawi Limited, 2010)
HDL, through sphingosine-1-phosphate (S1P), exerts direct cardioprotective effects on ischemic myocardium. It remains unclear whether other HDL-associated sphingophospholipids have similar effects. We therefore examined if HDL-associated sphingosylphosphorylcholine (SPC) reduces infarct size in a mouse model of transient myocardial ischemia/reperfusion. Intravenously administered SPC dose-dependently reduced infarct size after 30 minutes of myocardial ischemia and 24 hours reperfusion compared to controls. Infarct size was also reduced by postischemic, therapeutical administration of SPC. Immunohistochemistry revealed reduced polymorphonuclear neutrophil recruitment to the infarcted area after SPC treatment, and apoptosis was attenuated as measured by TUNEL. In vitro, SPC inhibited leukocyte adhesion to TNFα-activated endothelial cells and protected rat neonatal cardiomyocytes from apoptosis. S1P3 was identified as the lysophospholipid receptor mediating the cardioprotection by SPC, since its effect was completely absent in S1P3-deficient mice. We conclude that HDL-associated SPC directly protects against myocardial reperfusion injury in vivo via the S1P3 receptor.